Prey composition impacts lipid and protein digestibility in northern fur seals ( Callorhinus ursinus ) - Diaz Gomez, Mariana; Rosen, David A.S.; Forster, Ian P.; Trites, Andrew W. (Canadian Journal of Zoology, 2020)
Pinnipeds have specific macronutrient (protein, lipid) requirements to satisfy physiological functions, yet little is known about how diet characteristics affect macronutrient digestibility. We measured relative and absolute lipid and protein digestibility in six female northern fur seals (Callorhinus ursinus (Linnaeus, 1758)) fed eight experimental diets composed variously of four prey species (Pacific herring, Clupea pallasii Valenciennes in Cuvier and Valenciennes, 1847; walleye pollock, Gadus chalcogrammus Pallas, 1814 (formerly Theragra chalcogramma (Pallas, 1814)); capelin, Mallotus villosus (Müller, 1776); magister armhook squid, Berryteuthis magister (Berry, 1913)). We quantified how digestibility was affected by proximate composition of the diet (% lipid or % protein), levels of food mass and macronutrient intake, and tested for any potential benefit of multi-species diets. Overall, digestibility of both protein and lipid were high across diets, although macronutrient retention of lipids (96.0%–98.4%) was significantly higher than protein (95.7%–96.7%) for all but the two highest protein diets. Increased levels of protein intake resulted in increased protein retention, but decreased lipid digestibility. There was no evidence that mixed-species diets provide greater macronutrient digestibility over single-species diets. The results suggest that high to moderate lipid diets are more beneficial to northern fur seals because they lead to increased levels of lipid retention without large decreases in protein digestibility. This raises concerns that dietary factors may be contributing to the population declines of northern fur seals in the Bering Sea.